Functional Nucleic Acid-Based Live-Cell Fluorescence Imaging - Zhang, Yutong; Du, Yulin; Zhuo, Yuting; Qiu, Liping (Frontiers in Chemistry, 2020)
Cell is the structural and functional unit of organism. It serves as a key research object in various biological processes, such as growth, ontogeny, metabolism and stress. Studying the spatiotemporal distribution and functional activity of specific biological molecules in living cells is crucial for exploring the mechanism governing life. It also facilitates the elucidation of pathogenesis, clinical prevention and disease theranostics. In recent years, the fluorescence imaging technique has been greatly exploited for live-cell imaging. However, the development of molecular probes has lagged far behind. Functional nucleic acids (FNAs), for example, aptamer and DNAzyme, possess special chemical and/or biological functions, hence severing as promising molecular tools for cellular imaging. The current mini review focuses on the applications of FNAs in live-cell fluorescence imaging.